2015
DOI: 10.1002/da.22398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Religious Versus Standard Cognitive-Behavioral Therapy on Optimism in Persons With Major Depression and Chronic Medical Illness

Abstract: RCBT and SCBT are equally effective in increasing optimism in persons with MDD and chronic medical illness. While baseline religiosity does not moderate this effect, religiosity predicts increases in optimism over time independent of treatment group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 51 publications
0
27
0
2
Order By: Relevance
“…Researchers suggest that optimism can be learned through different intervention strategies (Koenig, Pearce, Nelson, & Daher, 2015). An intervention to increase the level of optimism in individuals with PD may help to reduce symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggest that optimism can be learned through different intervention strategies (Koenig, Pearce, Nelson, & Daher, 2015). An intervention to increase the level of optimism in individuals with PD may help to reduce symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria are as follow: Age ≤ 65 years, having undergone first-time CABG surgery (4 weeks after surgery), having received follow-up treatment in Tuba Clinic, fluency in Farsi, junior high school degree, or higher level of education, willingness to participate and provide written consent, meeting the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria for anxiety and depression ( 39 ), Score ≥ 8 for anxiety and depression on the Persian version of the Hospital Anxiety and Depression Scale (HADS)( 40 ), and being religious (based on self-reports) ( 32 ). The exclusion criteria are as follow History of psychiatric disorders such as schizophrenia, bipolar disorder, and serious suicidal thoughts confirmed by clinical interviews performed by a psychiatrist based on the DSM-IV history of any physical conditions preventing the patients from participating in treatment sessions, history of attending RCBT, CBT, or any other types of psychotherapy programs, and using sertraline during the 2-week period prior to the study.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, research has indicated the higher efficacy of nonpharmacological treatments with religious approaches in reducing depression and anxiety ( 28 - 31 ). However, the results showed different efficacies for conventional cognitive behavioral therapy (CCBT) and RCBT methods such that some studies have reported the same efficacies for CCBT and RCBT ( 32 ), and others found RCBT more effective than CCBT ( 33 ). Meanwhile, the results obtained showed that RCBT is slightly more effective than CCBT in more religious patients with depression and physical illness ( 34 ).…”
mentioning
confidence: 99%
“…In a study of patients with major depression, we found that, although religiosity was unrelated to depressive symptoms, there was a striking positive correlation with positive emotions (Koenig 2014). Furthermore, in the clinical trial described above, RCBT tended to be more effective in increasing optimism than in decreasing depressive symptoms (Koenig 2015b).…”
Section: Faith and Qolmentioning
confidence: 99%